Gestión de ingresos en la Empresa Coagrimsa S. A año 2021. - Chica Murillo, Mariuxi Beatriz (2022)
The following case study is called "income management in the company COAGRIMSA S. A YEAR 2021 where financial information for the period 2020-2021 will be analyzed" was The purpose of this work is to know the financial management of the company, it has a impact on the profitability achieved during the previous period, and during 2021, the entity did not have any problem. To carry out this research, the interview technique was used, which allows the collection of sufficient information to carry out, and the application of financial instruments that help to evaluate the incidence of income and expenses in profitability, as well as in known financial ratios such as markup, ROA, ROE, current ratio, cash ratio, accounts receivable total debt ratio. Additionally, horizontal analysis was used to view company revenues and expenses for 2020 and 2021. Of the two periods analyzed, the most complex was 2020 of the company COAGRIMSA SA, compared to the year 2021 where the company recovers its money, this situation affects the profitability of the entity, as evidenced by applying these financial ratios.